Has Outcome of Subarachnoid Hemorrhage Changed With Improvements in Neurosurgical Services?: Study of 2000 Patients Over 2 Decades From India. Issue 12 (December 2018) - Dhandapani, Sivashanmugam; Singh, Apinderpreet; Singla, Navneet; Praneeth, Kokkula; Aggarwal, Ashish; Sodhi, Harsimrat B.; Pal, Sudhir S.; Goudihalli, Sachin; Salunke, Pravin; Mohindra, Sandeep; Kumar, Ajay; Gupta, Vivek; et al.
Abstract : Background and Purpose—: Though reports suggest decreasing fatality rates of subarachnoid hemorrhage with time, trends in outcome are not reported much especially from developing countries. This study was to analyze changes in outcome across 2 decades and elucidate probable factors. Methods—: Prospective databases during 1996 to 2015 were reviewed for neurological outcome at 3 months in relation to demographics, Hunt and Hess grade, Fisher grade, and definitive treatment; and compared between 2 decades, contrasted by establishment of intensive care unit with continuous monitoring and other advancements. Univariate and multivariate analyses were performed. Results—: Of the total 2039 patients, 1035 were managed in the former and 1004 in the recent decades. Compared with the former decade, there is delayed age at presentation (46 versus 49 years, P <0.001), poorer Fisher grades (81% versus 87%, P <0.001), and more patients with Hunt and Hess grade 2 (24% versus 39%, P <0.001) in the recent decade. While all patients in databases of the former decade had undergone clipping, 6% in the recent decade underwent coiling. 11% in the recent decade could not undergo definitive treatment. Despite this, there was significantly higher overall favorable outcome (50% versus 60%; odds ratio, 1.5; P <0.001) in recent decade. Favorable outcome of surgical clipping per se improved significantly from 50% to 67% (odds ratio 2.0; P <0.001). Though the improvement was across subgroups, it was more marked among Hunt and Hess grade 3 and Fisher grades 3 and 4. In multivariate analyses, both overall outcome (adjusted odds ratio, 1.7; 95% CI, 1.4–2.1; P <0.001) and surgical outcome (adjusted odds ratio, 1.8; 95% CI, 1.5–2.2; P <0.001) were significantly better in recent decade, independent of known prognostic factors. Conclusions—: This is probably the first report to show independent improvement in outcome of subarachnoid hemorrhage with betterment in neurosurgical services from developing country. Dedicated intensive care unit care and focused management protocols could be the likely causes for improvement. Resource-constrained institutions may target patients in Hunt and Hess grade 3 and Fisher grades 3 and 4 for optimal intensive care unit utilization.